Labour composition for maintenance works in Public Hospital built environment in South-West, Nigeria - O.A. Adenuga, (Penerbit UKM, 2010)
The study examined the labour composition for maintenance works in the public hospital buildings in South-West, Nigeria, and in the process identified if there are any significant differences in the execution of maintenance works using outsourcing and in-house labour. In achieving the objective, the study adopted research survey technique with a total of 552 questionnaires comprising 206 for maintenance staff and 346 for users of public hospital collected and used for the study. The survey covered 46 public hospitals representing 40% of the total number of public hospitals existing in South-West, Nigeria. It comprises all the 11 federal owned hospitals and 35 selected states owned based on stratified random sampling technique. Data collected were analysed using descriptive and inferential statistics. The findings of the study revealed that there is no variation in the work performed by the use of in-source and outsourced labour. However, maintenance staff rated the use of in-source better than outsource in that it is found to produce higher quality and better quality control of services, reduction in cost while outsourced gives an understanding of latest technologies with better access to special skills. Based on the above findings, the study recommends that maintenance staff should be well motivated. For optimum results, maintenance departments need to adopt sound policies, as this will provide appropriate basis for preparing budgets that will meet the actual maintenance needs of the hospital buildings and services. Maintenance managers are to do their best to prepare realistic need-based budgets while the government should make efforts to improve funding for hospital maintenance. Inefficiencies and inflexibility through the imposition of bureaucratic impediments to operational effectiveness should be avoided in hospital environment due to the sensitivity of the services being rendered. Maintenance staff and users of hospital buildings should be given opportunities for further training on their jobs also on effective use of hospital facilities.